2023
DOI: 10.1039/d3cc04563c
|View full text |Cite
|
Sign up to set email alerts
|

ArI(NTf2)2: the boundary of oxidative capacity for ArIL2?

Lachlan Barwise,
Jason D. Bennetts,
Keith F. White
et al.

Abstract: Synthesis and crystallographic characterization of NO2-C6H4-I(NTf2)2 (NTF2 = bistriflimide) is reported. Experimental results find that this compound can perform oxidation reactions that ArI(OTf)2 is unable to and theoretical analysis indicates...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…4). 44 NTf 2 − is less coordinating than OTf − and in line with 45 These studies indicated that the [ArI] 2+ fragment abstracts uorine from the previous 3 anions and for the more robust peruorinated carborane anion, the theoretically predicted oxidative capacity is "off the charts". This led to the conclusion that ArI(NTf 2 ) 2 is likely, although not certainly, the boundary for oxidative capacity of ArIL 2 .…”
Section: The Myth and Redemption Of Ari(otf)mentioning
confidence: 73%
“…4). 44 NTf 2 − is less coordinating than OTf − and in line with 45 These studies indicated that the [ArI] 2+ fragment abstracts uorine from the previous 3 anions and for the more robust peruorinated carborane anion, the theoretically predicted oxidative capacity is "off the charts". This led to the conclusion that ArI(NTf 2 ) 2 is likely, although not certainly, the boundary for oxidative capacity of ArIL 2 .…”
Section: The Myth and Redemption Of Ari(otf)mentioning
confidence: 73%